Praktik Media Promosi Kesehatan Sebelum dan Setelah Pembelajaran Berbasis Digital - Asri Jumadewi; Fahmi Ichwansyah; Asmanidar; Putro Simeulu (Postgraduate, University of Mataram, 2026)
Health promotion media is a communication tool designed to accelerate education towards sustainable development (SDGs) in the health sector. Digital learning is an option to reduce limitations in the learning process. This study aims to determine the effectiveness of knowledge of health promotion media before and after digital learning. The research method is a pre-experiment with a one-group pretest-posttest design without control. The number of samples was 38 Level I students in the odd semester of the 2026/2027 academic year, obtained by purposive sampling. The data collection method used a critical knowledge instrument in the form of a questionnaire. The results of the normality test showed that the data were not normally distributed, with a Wilcoxon pairwise correlation test p-value <0.05, meaning there was a difference in the average ability of participants in knowledge of health promotion media before and after digital learning. The average grouping of student knowledge based on the N-Gain value ≥0.30, namely 0.33 - 1.00, concluded that students' abilities in knowledge of health promotion media after effective digital learning improved better (medium category). This is because digital learning is a supporting factor in the health education movement.